Potassium Channel Activator Attenuates Salicylate-Induced Cochlear Hearing Loss Potentially Ameliorating Tinnitus - Sun, Wei; Liu, Jun; Zhang, Chao; Zhou, Na; Manohar, Senthilvelan; Winchester, Wendy; Miranda, Jason A.; Salvi, Richard J. (Frontiers in Neurology, 2015)
High dose sodium salicylate causes moderate, reversible hearing loss and tinnitus. Salicylate-induced hearing loss is believed to arise from a reduction in the electromotile response of outer hair cells (OHCs) and/or reduction of KCNQ4 potassium currents in OHCs which decreases the driving force for the transduction current. Therefore, enhancing OHC potassium currents could potentially prevent salicylate-induced temporary hearing loss. In this study, we tested whether opening voltage-gated potassium channels using ICA-105665, a novel small molecule that opens KCNQ2/3 and KCNQ3/5 channels, can reduce salicylate-induced hearing loss. We found that systemic application of ICA-105665 at 10 mg/kg prevented the salicylate-induced amplitude reduction and threshold shift in the compound action potentials recorded at the round window of the cochlea. ICA-105665 also prevented the salicylate-induced reduction of distortion products of otoacoustic emission (DPOAE). These results suggest that ICA-105665 partially compensates for salicylate induced cochlear hearing loss by enhancing KCNQ2/3 and KCNQ3/5 potassium currents and the motility of OHCs.